2022
DOI: 10.1002/smll.202200364
|View full text |Cite
|
Sign up to set email alerts
|

3D Bioprinted GelMA‐Nanoclay Hydrogels Induce Colorectal Cancer Stem Cells Through Activating Wnt/β‐Catenin Signaling

Abstract: two-tailed unpaired t-tests for comparisons of two groups. Significant differences between groups were noted as follows: * for p < 0.05, ** for p < 0.01, and n.s, not significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…1 d,e). LGR5 and CD133 are well-known CSCs markers [ 20 ]. Then, we identified and sorted epithelial cells (EpCAM +) [ 21 ] and stem cells (EpCAM + /CD133 + , EpCAM + /LGR5 +) from the GC and GM populations (Figure S 1 a, b).…”
Section: Resultsmentioning
confidence: 99%
“…1 d,e). LGR5 and CD133 are well-known CSCs markers [ 20 ]. Then, we identified and sorted epithelial cells (EpCAM +) [ 21 ] and stem cells (EpCAM + /CD133 + , EpCAM + /LGR5 +) from the GC and GM populations (Figure S 1 a, b).…”
Section: Resultsmentioning
confidence: 99%
“…However, the relatively low mechanical properties of pure silk fibroin hydrogels limited the clinical applications. According to previous investigations, two-dimensional (2D) clay nanosheets could improve the hydrogel mechanical strength. Therefore, 2D mica–Fe 3 O 4 (MF) nanosheets as an artificial peroxidase were synthesized and employed to prepare the silk fibroin nanozyme hydrogel. The method for nanozyme hydrogel preparation is illustrated in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the mechanism governing stemness regulation was investigated, and GelMA-nanoclay hydrogel-activated Wnt/-catenin signaling was found to contribute to the induction and enrichment of CSCs. 78 To construct a TME, normal stromal cells were activated and reprogrammed into tumor-related stromal cells. Their results showed that tumor-related markers were overexpressed by the activated stromal cells, and they modified the ECM.…”
Section: Case Studies Of Bioprinting Cancermentioning
confidence: 99%
“…In conclusion, this model is appropriate for CRC tumor biology research studies and the creation of highly personalized cancer treatments. 2,77,78 Glioblastoma multiforme (GBM)…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%